Faktor Klinis yang Berperan terhadap Infeksi pada Pasien dengan Water Seal Drainage - Ika Veronita; Moh. Dwi Puspa Setiawan; Moh. Setya Puspa Kurniawan (Quantum Wellness : Jurnal Ilmu Kesehatan, 2025)
This study is based on problems that often occur in patients at NU Mangir Hospital with the aim of this study as an effort to detect several possibilities that occur so that it becomes a solution to minimize existing symptoms. This study uses quantitative research with the type of data collection taken based on random sampling techniques from existing patients and then analyzed using statistics with the help of SPSS version 20.00. Infection in patients with Water Seal Drainage (WSD) is a serious problem that increases morbidity and mortality. This study aims to identify demographic and clinical factors that influence the incidence of infection in WSD patients at NU Mangir Hospital, Banyuwangi. The method used is a cross-sectional approach with purposive sampling of 24 respondents. The results showed that systemic infections occurred most often (45.8%), and age factors, length of WSD installation, leukocyte levels, and comorbidities were significantly related to the incidence of infection. Improvement in the quality of care is needed to reduce the risk of infection.